HUBUNGAN MOTIVASI KERJA DAN KEMAMPUAN PENGUASAAN MATERI DENGAN KINERJA GURU DI KABUPATEN PANDEGLANG - samudi samudi (STIT Al-Marhalah Al-Ulya Bekasi, 2021)
This research is motivated, among others, by the work motivation of the aqidah akhlak teacher who has not met the expectations of all parties, the teacher is still limited in the ability to master the subject matter in the field of aqidah morals and the teacher's performance is still not optimal in the learning process for students.This study aims to determine, analyze and formulate the correlation between work motivation and the ability to master the material together with the performance of teachers in the field of study aqidah morals. The location of this research is at Madrasah Tsanawiyah in Pandeglang, Banten.This study used a survey method with correlational data analysis. The research sample consisted of 35 teachers, while data collection used observation, interviews, questionnaires and tests.The findings of this study are that there is a positive and significant correlation between work motivation and the ability to master the material together with teacher performance with a multiple correlation coefficient of 0.882. This means that work motivation and mastery of material have provided positive and significant support to teacher performance.The conclusion is that the higher the work motivation which includes; responsibility, achievement, self-development and independence and the ability to master the material which includes cognitive, affective and psychomotor, the higher the teacher's performance which includes; planning in teaching, classroom management, learning and evaluation.Â Keywords: Work Motivation, Material Mastery Ability, Teacher Performance